2018
DOI: 10.1016/j.bbmt.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Patients in Setting a Patient-Centered Outcomes Research Agenda in Hematopoietic Cell Transplantation

Abstract: The goal of patient-centered outcomes research (PCOR) is to help patients and those who care for them make informed decisions about healthcare. However, the clinical research enterprise has not involved patients, caregivers, and other non-providers routinely in the process of prioritizing, designing and conducting research in hematopoietic cell transplantation (HCT). To address this need, the National Marrow Donor Program (NMDP)/Be The Match® engaged patients, caregivers, researchers and other key stakeholders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionmentioning
confidence: 99%
“…The highest level of engagement was reported in four of 30 studies (13%) where collaboration was demonstrated across all four stages of the research cycle (see Table 4). Patients in these studies partnered in activities including, but not limited to: delineation of the scope of the partnership, contribution to study design, co-leadership on working groups during study execution, data analysis, dissemination activities, and adoption of decision-making roles on research steering/advisory committees [50,52,57,66]. Seven studies (23%) included patients in research priority setting at the broader level of biomedical specialty/ disease/condition, rather than at the individual study level [48,49,54,58,61,67,68].…”
Section: Patient Partner Research Roles: Research Stages and Activitiesmentioning
confidence: 99%
“…36 Robust studies evaluating the treatment of anxiety, depression, PTSD, neurocognitive dysfunction, and fatigue lack focus on thoroughly understanding the psychological and emotional challenges faced by HCT survivors more than 1 year post-HCT. 38 In response to this dearth of data, the National Marrow Donor Program (NMDP)/Be The Match developed a patient-centered outcomes research (PCOR) agenda for the HCT community; 1 of the 6 working groups will focus on the emotional, cognitive, and social health of HCT survivors. This working group developed priority research questions, several of which included evaluation of the impact of various behavioral and pharmacologic interventions on the cognitive function, mood, and QOL of survivors at least 1 year after HCT.…”
Section: Neuropsychological Effectsmentioning
confidence: 99%
“…This working group developed priority research questions, several of which included evaluation of the impact of various behavioral and pharmacologic interventions on the cognitive function, mood, and QOL of survivors at least 1 year after HCT. 38 The results of this focused research around patient-centered outcomes will be vital and valuable for the HCT community, patients, and providers, alike.…”
Section: Neuropsychological Effectsmentioning
confidence: 99%
“…LGBT needs has been recognized as a gap by the NMDP in the Patient-Centered Outcomes Research Agenda, their current standards provide no further guidance for caring for the transgender population [11]. Concurrently, FDA regulations relating to hematopoietic stem cells are regulated under 21 CFR 1271.3(d) (1) and Section 361 of the PHS Act and make no mention of gender or sex of donors.…”
mentioning
confidence: 99%